2021
DOI: 10.3390/ijerph182312850
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Environmental Regulations on Tourism Carbon Emissions

Abstract: This research analyzed the impact of environmental regulations and their power in suppressing tourism carbon emissions. The results showed that: (1) four types of environmental regulations had significant inhibiting effects on tourism carbon emissions, but different types of regulations had varying effects; and (2) environmental regulations had a significant time lag effect on tourism carbon emissions. The decay rates of the environmental regulation effects were dissimilar for supervisory management, market in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Carbon emission assessments are mainly based on a “top-down” perspective on the energy supply side [ 32 ] and a “bottom-up” perspective on the energy consumption side [ 33 ]. Research on carbon emissions in the tourism industry using the “bottom-up” approach focuses on the consumption side and assesses emissions by studying the energy consumption coefficient per unit of the output of various transportation modes [ 34 ], travel hotels [ 35 ], and tourist activities [ 36 ].…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…Carbon emission assessments are mainly based on a “top-down” perspective on the energy supply side [ 32 ] and a “bottom-up” perspective on the energy consumption side [ 33 ]. Research on carbon emissions in the tourism industry using the “bottom-up” approach focuses on the consumption side and assesses emissions by studying the energy consumption coefficient per unit of the output of various transportation modes [ 34 ], travel hotels [ 35 ], and tourist activities [ 36 ].…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…Based on the STIRPAT model, Shahbaz et al, analyzed the impact of Malaysia's urbanization rate, affluence, and trade openness on energy consumption, and found that the main factor affecting the growth of energy consumption is urbanization [18]. In addition, some scholars have analyzed the impact of foreign trade [19], environmental regulation [20], and financial development [21] on carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, scholars have explored the influence mechanisms of TET from different perspectives, including environment-led, organization-led, and technology-led. Some scholars believe that environmental regulation significantly impacts TET (Chen et al, 2021;Zha et al, 2021). Chen et al (2021) demonstrate that environmental regulation can suppress tourism carbon emissions, promote industrial structure upgrading, and promote TET.…”
Section: Introductionmentioning
confidence: 99%